Implementing Discipline in the Covid-19 Period in Improving Student Achievement - Amirzan Amirzan; Muhammad Muhammad; Jafaruddin Jafaruddin; Herizal Herizal; Muhammad Iqbal; Ilyas Ilyas (UNIVERSITAS SERAMBI MEKKAH, 2021)
This study aims to find out how to implimentation the discipline in schools to improve student learning achievement during the Covid-19. The research approach is qualitative. The population in this study was the principal, teacher council board and second grade students totaling 99 people. All data sources are research informants (total sample). Data collection techniques were carried out by means of interviews, documentation, observations and questionnaires which were circulated to each respondent who had been recorded as the research sample. The data analysis technique used descriptive method, with the aim of seeing the situation or facts that are currently developing. While data processing used non-parametric statistics by calculating the percentage of respondents' answers to each item and interpreting and tabulating the percentage formula. Based on the results of the research, it can be concluded that efforts to enforce student discipline can be carried out properly, with cooperation between teachers and parents, so that a student life can be patterned that is full of discipline and obeys school regulations, so that online learning in the Covid 19 era can have a positive impact on student learning developmen